Masculinity in Indonesian Popular Culture in the Early Era of the New Order Regime - Ferry Fauzi Hermawan (Lingua Cultura, 2017)
This study aimed to identify the forms of masculinity in the Indonesian popular culture in the beginning of New Order regime. This study was based on the two novels: Cross Mama and Kekasih-Kekasih Gelap, written by Motinggo Busye. The analysis used new historicism theory proposed by Stephen Greenblatt. The analysis also considered various cultural contexts emerged in 1970s. The results show three shared trends in the novels. The first trend shows that the masculinity tends to be represented by both men worshiping patriarchal values such as the myth of woman’s virginity and men perceiving woman as a sexual object. The second trend shows that masculinity is stereotyped based on masculinity, power, and male dominance. The third trend shows that masculinity relates to various products of mass culture at the time. This last trend shows that in that era,the ideal male figure is represented as the one who: (1) is sexually active with many women, (2) has a muscular body, (3) has a handsome look, and (4) has a financial capability. Besides the shared three trends, the result also shows that the texts in the novels do not only reflect the cultural situations in the 60’s and 70’s but also contribute in shaping the social values of the cultural situations.